(untitled) (Chemical Engineering Research Bulletin, 2021)
Fire accidents are very frequent and a major issue in Bangladesh in recent times. In this paper fire growth behavior in an apartment building is studied through a numerical analysis using Fire Dynamic Simulator (FDS). A model apartment with fixed combustibles was created using FDS. The fire growth characteristics were studied and heat release rate, the rise of temperature, toxic gas dispersion and human evacuation were assessed. The fire was generated using a burner function. Computational analysis results from those models were analyzed and discussed. The relationship of wind and ventilation effect with time helps to predict the fire growth behavior in different location of the apartment. Evacuation modeling was created to illustrate the effect of evacuation time and fractional effective dose (FED) for different types of agents. FED is the summation of toxic gas consumption which is important for safe evacuation. The results show that the ventilation effect releases the heat and makes the apartment less vulnerable. Elderly people took more time for total evacuation than other groups that related to FED percentage. The idea of critical door length is demonstrated for safe evacuation during fire emergencies. Chemical Engineering Research Bulletin 21(2020) 99-105